C-C Chemokine Receptor Type 2–Dependent Migration of Myeloid-Derived Suppressor Cells in Protection of Islet Transplants. Issue 8 (August 2017) - Qin, Jie; Arakawa, Yusuke; Morita, Miwa; Fung, John J.; Qian, Shiguang; Lu, Lina
Abstract : Background: Islet transplantation is a promising therapeutic approach to restore the physical response to blood glucose in type 1 diabetes. Current chronic use of immunosuppressive reagents for preventing islet allograft rejection is associated with severe complications. In addition, many of the immunosuppressive drugs are diabetogenic. The induction of transplant tolerance to eliminate the dependency on immunosuppression is ideal, but remains challenging. Methods: Addition of hepatic stellate cells allowed generation of myeloid-derived suppressor cells (MDSC) from precursors in mouse bone marrow. Migration of MDSC was examined in an islet allograft transplant model by tracking the systemic administered MDSC from CD45.1 congenic mice. Results: The generated MDSC were expressed C-C chemokine receptor type 2 (CCR2), which was enhanced by exposure to interferon-γ. A single systemic administration of MDSC markedly prolonged survival of islet allografts without requirement of immunosuppression. Tracking the administered MDSC showed that they promptly migrated to the islet graft sites, at which point they exerted potent immune suppressive activity by inhibiting CD8 + T cells, enhancing regulatory T cell activity. MDSC generated from CCR2 −/− mice failed to be mobilized and lost tolerogenic activity in vivo, but sustained suppressive activity in vitro. Conclusions: MDSC migration was dependent on expression of CCR2, whereas CCR2 does not directly participate in immune suppression. Expression of CCR2 needs to be closely monitored for quality control purpose when MDSC are generated in vitro for immune therapy. Abstract : The protection role of exogenous myeloid-derived suppressor cells (MDSC) on islet graft has been explored in a mouse model. The migration of systemic injected MDSC to islet graft site is CCR2 dependent. Supplemental digital content is available in the text.